Expectations of students of different age groups in Agricultural Technician the Professional Education - Both, Vanderlei (2013)
It is proposed from this investigative study to analyze the expectations of entering students of technical course in Agriculture, with different age groups, as the contribution of professional education for its professionalism and continued education. A mixed questionnaire was applied and, to evaluate the data, the group was divided into two categories. Differences in their school history were evidenced, as well as their expectations regarding the course. The younger students have a tendency to be conducting the course because they could not join a college. On the other hand, older students seek in technical knowledge to act professionally or to be a complement of their graduation. Thus, the teachers and the school need to strengthen the possibilities that the course provide, in order to stimulate the course ending, in order to form professionals to contribute to the community.